Evaluation of skin elasticity after used different seaweed containing products by DermaLab® Combo - Wan Sulaiman, Wan Mohd. Azizi; Azad, Abul Kalam; Daud, Nurul Amirah; Sunzida, Nushrat Khan (Asian Journal of Pharmacy and Pharmacology, 2016)
Objective: This particular study aims to investigate the effect of different local antiageing products on the barrier function of normal skin, as measured by quality of skin elasticity. Methods: The elasticity probe of DermaLab® Combo Series assesses the effectiveness of three local anti-aging products by measuring the pressure needed for the suction pump to elevate skin. In this study, 15 female volunteers were divided into three groups, which corresponded with three different brands of moisturizers. The volunteers were treated with one test preparation on one volar forearm twice daily for 4 weeks, while leaving the other forearm untreated to serve as the control. After 4 weeks, both volar forearms, treated and control, were assessed for the measurement of skin elasticity by using DermaLab® Combo, and the readings were compared to the baseline. Results: Brand B shows the greatest percent increase in skin elasticity with the value of 96.44%, followed by Brand C (95.16%) and Brand A (39.02%). The result implies that Brand B gives the best anti-aging effect to the consumers regardless of subject compliance. This is relatively acceptable since the difference in percentage increase of skin elasticity between the highest reading and the lowest reading is near to each other except for Subject B1. The result portrayed by Subject B1 reflects his compliance problem during product application phase as mentioned during final skin assessment. In case of Brand C, a large gap is seen between the highest (468.8%) and the lowest (-26.5%) percentage increase in skin elasticity. Conclusions: The application of seaweedcontaining antiaging products leads to improvement in skin elasticity as measured by DermaLab® Combo Series.